Biparental inheritance of germline-specific chromosomes in the sea lamprey and their roles in oocytes - Vladimir A. Timoshevskiy; Nataliya Timoshevskaya; Kaan I. Eşkut; Kasturi Rajandran; Jeramiah J. Smith (Proceedings of the National Academy of Sciences, 2025)
Many eukaryotic species undergo programmed elimination of specific chromosomes during embryogenesis, typically retaining these chromosomes only in their germ cells. In some species, programmatic elimination of GRCs, or sex chromosomes, also occurs in a sex-specific manner, with specific chromosomes being transmitted or eliminated by only one sex. As such, these chromosomes provide a unique perspective on the evolution of gene functions that are advantageous to the germline and genetic tradeoffs between somatic vs germline or oocyte vs sperm biology. While GRCs have been extensively characterized in male sea lampreys ( Petromyzon marinus ), the status of GRCs in females has not yet been resolved, though it has been hypothesized that male-specific expression/transmission of these chromosomes might provide a solution to resolving the long-standing mystery of lamprey sex determining mechanisms. To gain insight into the roles of GRCs in female lampreys, we performed several karyological, transcriptomic, and genomic analyses, which demonstrate that GRCs are present in the female lamprey germline, transmitted by oocytes and somatically eliminated in both sexes. These analyses also show that GRCs play important roles in the maintenance and development of female germline but provide no evidence for sex-specific variation in the elimination and transmission of lamprey GRCs. These findings underscore the diversity of germline functions that are carried out by GRCs in both male and female lampreys and highlight the fact that sex-specific transmission/retention of GRCs likely follows no universal rules across the diverse lineages that have independently evolved to undergo developmentally programmed DNA elimination.